Odontologia baseada em evidência: etapas e métodos de uma revisão sistemática - Zina, Lívia Guimarães; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2012)
Evidence-based science uses epidemiological study models with the aim of applying scientific knowledge in health decisions. As such, the present study aimed to describe and discuss Evidence-Based sDentistry (EBD) and the methodology of systematic reviews, highlighting the steps needed to execute these, such as the formulation of search strategies, the definition of inclusion and exclusion criteria, data abstraction, as well as analysis and synthesis, including meta-analysis. The EBD is understood as an approach to oral health care that requires the integration of scientific evidence with the professional's expertise and the population's needs. As a contribution, the EBD has introduced methods which generate evidence of quality, statistical tools used to synthesize and analyze the evidence (systematic reviews and meta-analysis), in addition to ways of accessing (electronic databases) and applying the evidence (evidence-based health decisions). Finally, the evidence-based approach allows for the evaluation of the scientific knowledge through its validity, impact, and applicability, eliminating the gap between research and the reality of health services. It is necessary that efforts continue to be employed in an attempt to stimulate qualitative advances in epidemiological research in the oral health field, in turn helping EBD reach a broader space within the processes of planning and implementation of healthcare actions.

A ciência baseada em evidência utiliza modelos de estudos epidemiológicos com a finalidade de aplicar o conhecimento científico nas decisões em saúde. O objetivo deste artigo foi descrever e discutir a Odontologia Baseada em Evidência (OBE) e metodologia das revisões sistemáticas, destacando as etapas para a sua realização, como a formulação de estratégias de busca, definição de critérios de inclusão e exclusão, extração, análise e síntese dos dados, incluindo a meta-análise. A OBE é compreendida como uma abordagem para o serviço de saúde odontológico que requer integração da evidência científica com a experiência do profissional e as necessidades da população. Como contribuição, a OBE introduziu métodos que geram evidência de qualidade, ferramentas estatísticas utilizadas para sintetizar e analisar a evidência (revisões sistemáticas e meta-análise) e modos de acessar (bancos de dados eletrônicos) e aplicar a evidência (decisões em saúde baseadas em evidências). Por fim, a abordagem baseada em evidência permite avaliar o conhecimento científico por sua validade, impacto e aplicabilidade, eliminando a lacuna entre pesquisa e realidade dos serviços de saúde. É necessário que esforços continuem sendo empregados no sentido de estimular avanços qualitativos na pesquisa epidemiológica, fazendo com que a OBE alcance cada vez mais seu espaço concreto nos processos de planejamento e execução das ações em saúde.
Evidence-based dentistry: steps and methods of a systematic review
Keywords: Evidence-based practice; Evidence-based dentistry; Epidemiology; Meta-analysis as a topic; Review; Methodology; Prática clínica baseada em evidências; Odontologia baseada em evidências; Epidemiologia; Metanálise como assunto; Revisão; Metodologia